1989
DOI: 10.1111/j.1464-5491.1989.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoke Tea, a Chinese Herbal Treatment for Diabetes Mellitus

Abstract: Xiaoke tea, a traditional Chinese treatment for diabetes mellitus, lowered blood glucose concentrations in streptozotocin diabetic mice. To investigate Xiaoke clinically, a double-blind crossover study was undertaken in 12 non-insulin-treated diabetic patients. Xiaoke tea and ordinary tea (infusion of 2.72 g, 4 times daily) were consumed in random order for 4 weeks. A standard breakfast meal was taken before and after each treatment period. Xiaoke did not significantly affect glycosylated haemoglobin, basal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…36 In the late 1980s, plant extracts from cerasee, 37 xiaoke tea, 38 agrimony, alfalfa, coriander, eucalyptus, and juniper 39 were all reported to have antihyperglycemic effects during the development of diabetes in mice. Recently, various hypoglycemic compounds have been identified, and different possible mechanisms were proposed for different plant extracts that could be preventive and/or curative in diabetic animal models.…”
Section: Discussionmentioning
confidence: 99%
“…36 In the late 1980s, plant extracts from cerasee, 37 xiaoke tea, 38 agrimony, alfalfa, coriander, eucalyptus, and juniper 39 were all reported to have antihyperglycemic effects during the development of diabetes in mice. Recently, various hypoglycemic compounds have been identified, and different possible mechanisms were proposed for different plant extracts that could be preventive and/or curative in diabetic animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 119 publications (published in 62 journals, 16 Chinese/Taiwanese and 46 others) one study was published twice: once in English [5] and once in Chinese [6]. Two theoretical papers [7,8] [26,[82][83][84][85][86][87], and 18 miscellaneous [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]. We found at least two publications in the following fields: angina pectoris, arterial occlusive disease, asthma, atopic dermatitis, chronic hepatitis, common cold, diabetes mellitus, esophageal precancerous lesion, herpes zoster, menopausal syndrome, rheumatoid arthritis, and aging process (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…More and better designed trials and possibly a systematic review of literature on TCP available in the Western world are needed. Wang [98] Chen [94] without name [93] Shen [92] Shi [67] Jiang [62] Wu [105] Hu [106] Liao [107] Fang [108] Li [68] Drabaek [64] Drabaek [63] Li [78] Hsieh [77] Worm [49] Ramgolam [38] Fung [48] Armstrong [47] Koo [46] Sheehan [44] Sheehan [43] Latchmann [42] Sheehan [40] Sheehan [41] Atherton [39] Batey [25] Akbar [24] Chen [14] Hirayama [13] Caceres [80] Scaglione [72] (continued) Chen [86] Liang [83] Hale [82] Chen [20] Tatsuta [19] Hou [17] Lin [6] Lin [12] Charuwichitratana [71] Sangkitporn [69] Davis [33] Hirata [32] Ding [30] Wang [28] Ramgolam …”
Section: Resultsmentioning
confidence: 99%
“…It appears not to affect insulin concentrations and was ineffective in rats that lack endogenous insulin. The trial did not report details about the constituents of the treatment tea, and investigators reported no difference in glycemic parameters as compared with an "ordinary" tea infusion (115). Another controlled clinical trial (n ϭ 148) examined a formulation called Semen Persical Decoction for Purgation with Addition (SPDPA), a combination of eight different herbs and reported decreases in fasting blood glucose not significantly different from changes seen with glyburide (116).…”
Section: Multiple Herb Combinations For Glycemic Controlmentioning
confidence: 99%